Diet recommendation for children with Failure to Thrive (FTT) using fuzzy expert system / Nurul Syakirah Suliman - Suliman, Nurul Syakirah (2017)
Parents with children that are diagnosed with FTT need to meet dietitian once in 3 months to check their children's growth. In between the consultation time, parents need to plan their own dietary plan in order to maintain the growth of their children. Without having a proper nutrition, children may get variety of medical or psychosocial problems. A recommendation system using fuzzy expert system is proposed to support parents in making right dietary plan for their own children. Incremental model is used to develop the proposed work. Five core phases which are preliminary study, data preparation, knowledge acquisition, implementation and evaluation are followed to make sure the system produce proper dietary plan. This system is evaluated by an expert who verify on dietary plan recommended by the system for 10 selected case studies. The evaluation results on 40% correct output with another 60% falls into the grey area. It shows that using fuzzy expert system for diet recommendation system can produce correct dietary plan. For future work, to produce diet recommendation system that are more reliable and widely used, the fuzzy range need to recalculated back and adding more data about children which can be used by children with FTT in different age.